Effects of methotrexate upon inflammatory parameters induced by carrageenan in the mouse model of pleurisy - Eduardo Monguilhott Dalmarco; Tânia Silvia Fröde; Yara Santos Medeiros (Mediators of Inflammation)
Background: The model of pleurisy induced by carrageenan exhibits a biphasic response (4 and 48 h) and permits the quantification of exudate, cell migration and certain enzymes such as myeloperoxidase (MPO) and adenosine-deaminase (ADA) that are markers of activated leukocytes.